Suicidal Ideation among Adults Aged 16-30 in Palestine - Al-Hallaq, Iyad Salim; Al-Rimawi, Omar Talib; Aameh, Katya Elias (Journal of Educational and Psychological Sciences, 2022)
This study aimed to investigate prevalence rate of suicidal ideation among adults aged 16-30 in Palestine. The research used the descriptive correlative approach, and the study tool was the suicidal ideation scale. This was accomplished through connecting it with the independent variables: age, sex, the marital state, the province, level of education and occupation. The sample of the study consisted of (1210) adults in Palestine. The study showed that the overall degree of suicidal ideation was (13.9%), and the proportion of people talk about about the attempted suicide was 7.8%, and 10.2% are thinking of suicide in the future. The study recommends paying attention to suicidal thoughts, which are detected early on suicide attempts. The importance of opening specialized centers to try to avoid suicide attempts.